2011
DOI: 10.1007/s12011-011-9103-0
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Serum Trace Elements and Heavy Metals with Carotid Artery Atherosclerosis in Maintenance Hemodialysis Patients

Abstract: Changes in essential trace elements and heavy metals may affect the atherosclerotic state of patients on maintenance hemodialysis (HD). The aim of the study was to evaluate the relation between the serum levels of some trace elements and heavy metals (iron, zinc, manganese, copper, magnesium, cobalt, cadmium, lead, and copper/zinc ratio) and carotid artery intima-media thickness (CIMT) in HD patients. Fifty chronic HD patients without known atherosclerotic disease and 48 age- and sex-matched healthy individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…Anorexia, low taste sensibility, glucose intolerance, healing difficulties, anemia, malnutrition, and cardiovascular disease are common features and complications of CKD that can be associated with these alterations [10,11,12,13,14]. The positive effects of these element supplements on CKD patients are also supported by some research studies [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anorexia, low taste sensibility, glucose intolerance, healing difficulties, anemia, malnutrition, and cardiovascular disease are common features and complications of CKD that can be associated with these alterations [10,11,12,13,14]. The positive effects of these element supplements on CKD patients are also supported by some research studies [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, patients are at risk for low dietary intake of such substances which is attributable to uremia-related anorexia and dietary restrictions. Based on these, some essential TEs may be deficient, thereby causing some complications, which may further lead to an acceleration in disease progression [10,11,12,13,14]. On the other hand, toxic TEs that present in dialysis fluids but not in blood may accumulate.…”
Section: Introductionmentioning
confidence: 99%
“…Increased carotid intimal medial thickness has been observed in association with increased serum lead levels in a Turkish population with concomitant renal disease 136 . Lead exposure has also been associated with reduced heart rate variability and abnormalities of cardiac structure and function, including increased left ventricular hypertrophy and decreased ejection fraction 131 .…”
Section: Leadmentioning
confidence: 94%
“…Cadmium has also been associated with cardiometabolic derangement including Type 2 Diabetes, as noted in a study from China 187 . Additionally, increased carotid intimal-medial thickness and carotid plaques also have been associated with cadmium exposure 136 .…”
Section: Cadmiummentioning
confidence: 99%
“…Some studies have suggested associations between trace element metabolism and inflammation, oxidative stress, or atherosclerosis in HD patients [44,46,47]. The effect of sevelamer on trace element metabolism should be examined by further studies.…”
Section: Effect On Trace Element Metabolismmentioning
confidence: 99%